P65 Failure to control hepatitis B virus replication despite control of human immunodeficiency virus replication in co-infected patients on tenofovir-containing ART regimen cause for concern in hepatitis B virus monoinfection?. (16th November 2010) - Joshi, D; Childs, K; Carey, I; Bruce, M; Al-Freah, M; Horner, M; Harrison, P; Suddle, A; Agarwal, K; Taylor, C
Abstract : Introduction: Cross-resistance between human immunodeficiency virus (HIV) and hepatitis B virus (HBV) can play an important role in failure to control HBV replication in co-infected individuals resulting in suboptimal control of HBV. Tenofovir (TDF) based therapy should be effective for suppression of both HIV and HBV replication. Aim: To evaluate HBV factors in HBV/HIV co-infected subjects with undetectable HIV and persistently detectable HBV following 48 weeks of TDF based anti-retroviral therapy (ART). Method: Our prospectively maintained clinical database was interrogated. 113 HIV/HBV coinfected patients were identified; 14 (12.4%) patients had detectable HBV DNA (but undetectable HIV RNA) after 48 weeks of TDF based ART. 8/14 (57%) were eAg +ve, 12 patients were male, median age was 44.2 (39.9, 48.8) yrs. Direct sequencing of HBV polymerase was performed at baseline and 48 weeks. HBV DNA (log10 IU/ml) testing with Roche Cobas Ampliprep/Taqman v2 (LL<20 IU/ml) at baseline and appropriate time-points. Results: Baseline median HBV DNA was 7.74 (5.1, 8.0) log10 IU/ml. HBV genotype was A in 7/14 (50%), E in 4 (29%), G in 2 (14%) and D in 1 pt. 9 pts (64%) had lamivudine (3TC) monotherapy for a median of 19.9 (8.3, 60.5) months prior to switching to a TDF regime; 3/9 pts also had a period of TDF monotherapy. All 14 patients received combination therapy of TDF and 3TC/FTC. At baseline 5/14 (36%) had evidence of 3TC resistance as shown by the M204V mutation alone or with L180M and/or V173L. 9/14 had no known mutations; no pt displayed TDF resistance. After 48 weeks of TDF based therapy HBV DNA was 1.95 (1.6, 3.2) log10 IU/ml, in 8/14 pts HBV DNA was <2 log10 IU/ml. HBV DNA became undetectable in 9/14 pts (64%) after median 175 weeks of therapy but 5/14 pts (36%) still had detectable HBV DNA a median of 199 weeks after TDF was started. At resistance testing after 48 weeks TDF: 8/14 pts had HBV DNA below limit of amplification, in 6/14 pts 2 showed persistent 3TC mutations, 1 pt showed wild type despite previous 3TC resistance and 3 showed no known mutations. No patient developed the A194T mutation conferring TDF resistance. Conclusion: Despite optimal adherence to TDF treatment, as evidenced by control of HIV, 14 pts failed to achieve undetectable HBV DNA after 48 weeks of treatment. In 5/14 pts, HBV DNA remained detectable at a low level nearly 4 years into TDF treatment, but no patient developed TDF HBV resistance. The long-term clinical significance of low level HBV viraemia in this population is unclear. This may be an HIV specific issue or reflect cumulative HBV resistance allowing replication fitness. Further investigation by phenotypic analysis and/or ultra-deep pyrosequencing is warranted.